Metabolic engineering of flavonoids in tomato (Solanum lycopersicum): the potential for metabolomics - Bovy, Arnaud (Springer US, 2007)
Flavonoids comprise a large and diverse group of polyphenolic plant secondary metabolites. In plants, flavonoids play important roles in many biological processes such as pigmentation of flowers, fruits and vegetables, plant-pathogen interactions, fertility and protection against UV light. Being natural plant compounds, flavonoids are an integral part of the human diet and there is increasing evidence that dietary polyphenols are likely candidates for the observed beneficial effects of a diet rich in fruits and vegetables on the prevention of several chronic diseases. Within the plant kingdom, and even within a single plant species, there is a large variation in the levels and composition of flavonoids. This variation is often due to specific mutations in flavonoid-related genes leading to quantitative and qualitative differences in metabolic profiles. The use of such specific flavonoid mutants with easily scorable, visible phenotypes has led to the isolation and characterisation of many structural and regulatory genes involved in the flavonoid biosynthetic pathway from different plant species. These genes have been used to engineer the flavonoid biosynthetic pathway in both model and crop plant species, not only from a fundamental perspective, but also in order to alter important agronomic traits, such as flower and fruit colour, resistance, nutritional value. This review describes the advances made in engineering the flavonoid pathway in tomato (Solanum lycopersicum). Three different approaches will be described; (I) Increasing endogenous tomato flavonoids using structural or regulatory genes; (II) Blocking specific steps in the flavonoid pathway by RNA interference strategies; and (III) Production of novel tomato flavonoids by introducing novel branches of the flavonoid pathway. Metabolite profiling is an essential tool to analyse the effects of pathway engineering approaches, not only to analyse the effect on the flavonoid composition itself, but also on other related or unrelated metabolic pathways. Metabolomics will therefore play an increasingly important role in revealing a more complete picture of metabolic perturbation and will provide additional novel insights into the effect of the introduced genes and the role of flavonoids in plant physiology and development.